Cálculo de huella de carbono de una planta de agua residual de un parque industrial ubicado en Malambo, Atlántico (2021)
Sanitation activities in Colombia emit 4% of total greenhouse gases, of which 1.3% is represented by the emission of Wastewater Treatment Plants. This research aims to estimate the carbon footprint of the wastewater treatment plant of an Industrial Park located in the municipality of Malambo, Atlántico. For this, the guidelines of the Greenhouse Gas Protocol Corporate Accounting and Reporting Standard (revised edition) of the World Resource Institute - WRI and the World Business Council for Sustainable Development WBCSD were taken as a reference, in which the following stages were structured: Phase A: Process characterization, Phase B: Emissions calculation, Phase C: Removal calculation and Phase D: Formulation of improvement strategies. It is concluded that the total emissions of Greenhouse Gases are 6925 TonCO2e / year for 2019, which is reduced to 6490TonCO2e / year due to the removals whose value is 434 Ton / hectare. In this sense, given these results, it is possible to infer that around 94% of the emissions emitted can be offset by 1 hectare of Roystonea Regia, finally these results suggest that it is probable that given the extensions in hectares of the industrial complex and starting from its biological diversity there could be a neutral emission.